De la conservation conflictuelle à l'aménagement durable : le paysage et la biodiversité saisis par le droit - Jean-Marie Breton (VertigO)
French law has belatedly interested in nature protection and conservation of the environment, through a legal process that has only gradually distinguished from the traditional legal disciplines, to endly differ significantly, while remaining largely in relation with them.The impact of the law upon the environmental issues and the formulation of normative responses to it answered the need for building and implementation of instruments fitting the objectives of protection both understood and interpreted by reference to a social vision of natural heritage, and adequate to the socio-cultural (with a wide identity dimension in the Caribbeans and Guyanas) of his apprehension by people as by developers and managers.Diachronic construction of relevant legal protection, particularly in terms of sustainability, exceeded the only normative approach in favor of the recognition of a real right to the environment, through its legislative and constitutional components. Today, positive law takes into account, beyond the mere "environment" considered in globo, both landscapes, subjected to specific legal treatment and protection ; and biodiversity, the conservation and management of which, because of its recognition as a conventional common heritage of mankind, in an intergenerational perspective, have raised legal arrangements ad hoc, at national as well as regional and international levels.